2019
DOI: 10.3390/ijms20040880
|View full text |Cite
|
Sign up to set email alerts
|

Carnosol as a Nrf2 Activator Improves Endothelial Barrier Function Through Antioxidative Mechanisms

Abstract: Oxidative stress is the main pathogenesis of diabetic microangiopathy, which can cause microvascular endothelial cell damage and destroy vascular barrier. In this study, it is found that carnosol protects human microvascular endothelial cells (HMVEC) through antioxidative mechanisms. First, we measured the antioxidant activity of carnosol. We showed that carnosol pretreatment suppressed tert-butyl hydroperoxide (t-BHP)-induced cell viability, affected the production of lactate dehydrogenase (LDH) as well as re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 31 publications
(17 citation statements)
references
References 42 publications
2
15
0
Order By: Relevance
“…Moreover, apoptosis of endothelial cells is an important factor of vascular injury, which is directly related to the degree of endothelial damage [59]. In the present study, we observed that oxLDL/β2GPI/anti-β2GPI complex increased the number of apoptotic cells and enhanced the expressions of proapoptotic proteins.…”
Section: Discussionsupporting
confidence: 61%
“…Moreover, apoptosis of endothelial cells is an important factor of vascular injury, which is directly related to the degree of endothelial damage [59]. In the present study, we observed that oxLDL/β2GPI/anti-β2GPI complex increased the number of apoptotic cells and enhanced the expressions of proapoptotic proteins.…”
Section: Discussionsupporting
confidence: 61%
“…CS is a polyphenolic compound with strong oxidative activity. 10,11 It had been reported that CS could promote the expression of Nrf2, 46,47 which would inhibit the activation of Smad pathway 48,49 and promote the mitochondrial respiration of cells. 50,51 Therefore, by acting as an antioxidant agent, CS might inhibit Smad3 pathway and promote mitochondrial respiration and thus ameliorate the increase in protein degradation as well as the decrease in protein synthesis in C2C12 myotubes treated with miR-183-5p.…”
Section: Discussionmentioning
confidence: 99%
“…HEK293-antioxidant response element (ARE) cell line previously established by our research group [ 29 ] was incubated with 275 traditional Chinese medicine (TCM) ingredients (10 μ M). Flex station 3 (Molecular Devices, San Francisco, CA, USA) was applied to detect the luciferase activity and discover the potential active ingredients.…”
Section: Methodsmentioning
confidence: 99%